Nanolithography on the Electron Beam Resist using the Scanning Probe Microscope Cantilever - Lydia Anggraini; Naoki Matsuzuka; Yoshitada Isono (Institute for Research and Community Services (LPPM) ITB, 2010)
This research demonstrates the feasibility of fabricating nanoscale resist patterns on a silicon (Si) substrate using a scanning probe microscope (SPM). In order to utilize scanning probe nanolithography (SPNL) with the other micro-machining techniques such as dry etching, plating and lift-off process, nanoscale resist patterns should be created on an Si substrate with high accuracy in SPNL. We have, so far, established the negative type of SPNL using the negative-tone electron beam (EB) resist named SAL601. The primary objective of this research is to find out appropriate process conditions for establishing the positive type of SPNL using the positive EB resist